2022
DOI: 10.25130/tjas.22.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield, and Quality Characteristics of Eight Winter Chickpea Varieties Under Rainfed Conditions

Abstract: This experiment was conducted aiming to introduce and select the suitable winter chickpea to Sulaymaniyah governorate climatic conditions. This study was laid out in RCBD design with eight different varieties (namely, FLIP 97-706C, FLIP 03-87C, FLIP 05-74C, FLIP 05-87C, FLIP 05-110C, FLIP 05-142C, FLIP 05-150C, and local Flip1 varieties), each with three replicates. The results indicated that the FLIP 97-706C variety had the highest yield (3531±2.1 kg ha-1), protein yield (390±0.05 kg ha-1), and weight of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Plant height is genotypic property and are affected by environmental conditions. With increasing plant height, leaf area per plant, number of leaves and assimilation increased (Vartanli and Emeklier, 2007). Plant height was higher first year than second year.…”
Section: Plant Heightmentioning
confidence: 92%
“…Plant height is genotypic property and are affected by environmental conditions. With increasing plant height, leaf area per plant, number of leaves and assimilation increased (Vartanli and Emeklier, 2007). Plant height was higher first year than second year.…”
Section: Plant Heightmentioning
confidence: 92%
“…In both research years, the lowest grain moisture values were obtained from the first year x V1 and second year x V1 interactions, and they took place in the same statistical group (e) (17.6 and 17.0 respectively) (Table 9). When previous studies on grain moisture at harvest were examined, it was observed that in general, the harvest grain moisture in early varieties was found to be lower than in late varieties (Kapar and Oz, 2006;Vartanli and Emekliler, 2007). The decrease in moisture in the grain after physiological maturation is closely related to physical factors.…”
Section: Grain Moisture and Grain Yieldmentioning
confidence: 97%